Claims Data Analysis on the Dispensing of Tricyclic Antidepressants Among Patients With Dementia in Germany - Hessmann, Philipp; Zeidler, Jan; Stahmeyer, Jona; Eberhard, Sveja; Vogelgsang, Jonathan; Abdel-Hamid, Mona; Wolff-Menzler, Claus; Wiltfang, Jens; Kis, Bernhard (Frontiers in Pharmacology, 2019)
Objective: A restrictive use of tricyclic antidepressants (TCA) in patients with dementia (PwD) is recommended due to the hazard of anticholinergic side effects. We evaluated the frequency of TCA dispensing in PwD over a period of one year and the use of TCA before and after the incident diagnosis of dementia. Methods: This analysis was based on administrative data from a German statutory health insurance for a period of two years. Totally, 20,357 patients with an incident diagnosis of dementia in 2014 were included. We evaluated the dispensing of TCA in 2015. Subgroup analyses were conducted to evaluate associations between the incident diagnosis of dementia and modifications in TCA dispensing. Results: In 2015, 1.125 dementia patients (5.5%) were treated with TCA and 31% were medicated with TCA in all four quarters of 2015. Most dispensings were conducted by general practitioners (67.9%). On average, patients received 3.7 ± 2.6 dispensing per year. Amitriptyline (56.3%), doxepin (26.8%), and trimipramine (16.8%) were dispensed most often. Subgroup analyses revealed that the dispensing of TCA remained mainly unchanged following the incident diagnosis. Conclusion: A relevant number of PwD were treated with TCA. To maintain the patients’ safety, an improved implementation of guidelines for the pharmaceutical treatment of PwD in healthcare institutions might be required. Since 68% of the patients suffered from depression, future studies should further evaluate the indications for TCA.